Microwave-Assisted Synthesis of the Quinolin-2(1H)-One Derivatives - Shaabani, Ahmad; Soleimani, Ebrahim; Mofakham, Hamid (Letters in Organic Chemistry, 2007)
The synthesis of quinolin-2(1H)-ones derivatives through a condensation reaction of 2-amino-benzophenones with α-mthylene esters under microwave-assisted conditions in high yield is described.
Keywords: knoevenagel condensation